2021
DOI: 10.1002/cpe.6586
|View full text |Cite
|
Sign up to set email alerts
|

Feature based opinion analysis on social media tweets with association rule mining and multi‐objective evolutionary algorithms

Abstract: Social media platform has achieved wide popularity in presenting the user-generated information online. The proliferation of user-generated content through social networking sites can enhance the existing transportation system. This work adds to the existing research by proposing a novel system to assess transit rider's reviews on the quality of transport services using Twitter information. A novel framework of a multi-objective evolutionary approach with association rule mining is proposed for feature-based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…what to eat in Fukuoka? : eat Fukuoka's Karashi Mentaiko (219), eat motsunabe at Rakutenchi (42), eat ramen in Fukuoka (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…what to eat in Fukuoka? : eat Fukuoka's Karashi Mentaiko (219), eat motsunabe at Rakutenchi (42), eat ramen in Fukuoka (25).…”
Section: Discussionmentioning
confidence: 99%
“…Similar approaches are presented in [22] [23], where the authors analyze tweets and predict political sentiment. An approach with the same aim extracts tweet features via adjectives and verbs to identify sentiment terms [24] [25]. The authors defined a set of rules to classify tweets according to the detected sentiment.…”
Section: B Syntactic Analysis Of Tweetsmentioning
confidence: 99%
“…They first generated a corpus of association rules and applied a multi-objective flower pollination algorithm to discover association rules for user opinions. The experimental results showed that their multi-objective cat swarm optimization algorithm outperformed other existing methods in terms of confidence and computational time [8]. Kota et al proposed a processing method for sentiment analysis datasets by combining LSTM and attention methods.…”
Section: Related Workmentioning
confidence: 99%
“…Through the above steps, the algorithm can build an efficient electrical data set model [24]. In the calculation steps of power grid data, the calculation method used in this study is power flow calculation, which follows Equation (8).…”
Section: Efficient Model Construction Of Rule Mining Based On Dwkm-ls...mentioning
confidence: 99%
“…Liu et al, recommended a collaborative dragonfly algorithm with a novel communication strategy, for the segmentation of multi-thresholding color images [31]. Meesala et al, proffered a feature-based emotion detection in social media, using multiobjective EAs [32]. Luo's group recommended a Whale Optimization Algorithm to reduce noise present in an image [33].…”
Section: Related Workmentioning
confidence: 99%